Manajemen Kurikulum dalam Meningkatkan Minat Entrepreneurship Peserta Didik Sekolah Menengah Kejuruan - Annisa Zauhar Nafisah; Yetri; Septuri (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Vocational education faces the challenge of producing graduates who are not only job-ready but also have the interest and courage to become entrepreneurs amid the limited availability of formal employment. The academic concern of this research stems from the fact that the choice of vocational high school (SMK) graduates to pursue entrepreneurship is still not dominant, thus requiring a strengthened curriculum management that can foster entrepreneurial interest in a more directed manner. This study aims to analyze curriculum management in enhancing entrepreneurial interest at SMK Negeri 1 Way Panji, South Lampung, and to identify its development strategies. The research employs a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that curriculum management is implemented through structured stages of planning, organizing, implementing, and evaluating. Planning is carried out by integrating entrepreneurial values into subjects, fieldwork practices, and activities based on local potential. Implementation is realized through theoretical and practical learning, entrepreneurship festivals, and student business projects. Evaluation is conducted periodically through process and product assessments. The implications of this study confirm that planned and collaborative curriculum management can strengthen the formation of vocational school graduates who are more independent, productive, and adaptive to changes in the world of work.